Datasets of demographic profile and perpetrator experience in committing crime among young offenders in Malaysia - Tharshini, N. K.; Fauziah, Ibrahim; Ezarina, Zakaria (Elsevier B.V., 2020)
The datasets in this article provides supplementary information related to: (1) demographic profile of young offenders and (2) perpetrator experience in committing a crime. A quantitative approach based on a cross-sectional survey design was employed to collect data among 306 young offenders undergoing Community Service Order initiated by the Malaysian Social Welfare Department. The resultant data were analysed descriptively using Statistical Package for the Social Sciences (SPSS). The result stipulates that the majority of respondents are consist of male young offenders aged 20 years old, Malays, single in marital status, and unemployed. Based on the crime involvement aspect, the result indicates that young offenders involved in stealing (26.1%), does not carry any weapons while committing a crime (50.0%), and entangled in criminal activity due to peer influence (40.0%). Moreover, unfavorable luck contributes to the failure in executing crime (52.6%) which subsequently leads them to be arrested by the police (52.0%).